Development and calibration of a dietary nitrate and nitrite database in the NIH–AARP Diet and Health Study. Issue 11 (2nd December 2015) - Inoue-Choi, Maki; Virk-Baker, Mandeep K; Aschebrook-Kilfoy, Briseis; Cross, Amanda J; Subar, Amy F; Thompson, Frances E; Sinha, Rashmi; Ward, Mary H
Abstract: Objective: Nitrate and nitrite are probable human carcinogens when ingested under conditions that increase the formation of N -nitroso compounds. There have been limited efforts to develop US databases of dietary nitrate and nitrite for standard FFQ. Here we describe the development of a dietary nitrate and nitrite database and its calibration. Design: We analysed data from a calibration study of 1942 members of the NIH–AARP (NIH–AARP, National Institutes of Health–AARP) Diet and Health Study who reported all foods and beverages consumed on the preceding day in two non-consecutive 24 h dietary recalls (24HR) and completed an FFQ. Based on a literature review, we developed a database of nitrate and nitrite contents for foods reported on these 24HR and for food category line items on the FFQ. We calculated daily nitrate and nitrite intakes for both instruments, and used a measurement error model to compute correlation coefficients and attenuation factors for the FFQ-based intake estimates using 24HR-based values as reference data. Results: FFQ-based median nitrate intake was 68·9 and 74·1 mg/d, and nitrite intake was 1·3 and 1·0 mg/d, in men and women, respectively. These values were similar to 24HR-based intake estimates. Energy-adjusted correlation coefficients between FFQ- and 24HR-based values for men and women respectively were 0·59 and 0·57 for nitrate and 0·59 and 0·58 for nitrite; energy-adjusted attenuation factors were 0·59 and 0·57 for nitrate and 0·47 and 0·38 for nitrite. Conclusions: The performance of the FFQ in assessing dietary nitrate and nitrite intakes is comparable to that for many other macro- and micronutrients.